Controlling the stability of high single-tier dumps in the ukrainian reconstruction context - Adamchuk, A. (Dnipro University of Technology, 2025)
The computer modeling technique was used using the "Slide" software to construct the most stressed sliding surfaces of the dumped rock massif. The obtained data for calculating the width of the prism of possible displacement were analysed and their dependence on the height of the single-tier dump and the water level in the intra-mine space was established by the least squares method. Застосовувалась методика компьютерного моделювання з використанням програмного забезпечення «Slide» для побудови найбільш напружених поверхонь ковзання відсипаного масиву гірських порід. Отримані дані розрахунків ширини призми можливого зрушення було проаналізовано і встановлено їх залежність від висоти одноярусного відвалу та рівня води у внутрішньокар’єрному просторі методом найменших квадратів.
Управління стійкістю високих одноярусних відвалів в контексті відбудови України
Keywords: internal dump; single-tier dump; physical and mechanical properties of rocks; dragline excavator; safety factor.; внутрішній відвал; одноярусний відвал; фізико-механічні властивості гірських порід; екскаватор-драглайн; коефіцієнт запасу стійкості.